Hate speech in new media spaces An analytical study of a sample of the religious discourse of the ""ISIS"" Via YouTube - djoudi, kherfia; djeffal, samia (Journal of Social Sciences and Humanities, 2021)
The use of social networking sites among extremist religious movements in Arab and Islamic environments is increasingly being used as a platform for rhetoric of violence and advocacy of extremism. Where social networks have always been an important tool in connecting youth and trying to integrate them into real collective action. This study will focus on the nature of the discourse of hatred in the organization of Dahesh, its superior media methods, its religious slogans and its permanent appeal to young people Muslim world for the establishment of the promised Islamic caliphate. All within the new social media. The sample of the study will be the modern media, specifically the YouTube network, through determining the levels of linguistic and semantic employment, and the mechanisms of language activation within the content of the media material provided on the YouTube site. This determination is made by relying on speech analysis methodology to study the text and its audio or visual symphony. To search for ways of operating the language and levels in the hate speech to organize the extremist Islamic state